Analisa Penggunaan Antibiotik Pada Pasien Pneumonia Anak Dan Remaja Di Rs Bhayangkara Lemdiklat Polri Periode Januari-Desember 2024 - Nurlela, Nurlela; Dewantoro, Agung; Susanti, Debi; Aulia, Gina (PHRASE (Pharmaceutical Science) Journal, 2025)
Pneumonia attacks the respiratory tract and is one of the dangerous infections that can potentially cause high mortality rates, especially in children and adolescents. The objective of this study were to analyze the pattern of antibiotics use in pediatric and adolescent pneumonia patients at an inpatient ward, Bhayangkara Lemdiklat Polri Hospital. Methods:This was a descriptive, observational and cross-sectional study. We employed a total sampling method, collecting data from patient medical records retrospectively. Results The findings revealed that most of the patients were toddlers, 0–5 years (43%) Table 1.Length of stay and distribution of pneumonia patients in MMCPS Age Prevalence n(%) Male Patient ratioTime interval Adult N=232 Working daysper dayRange (year) 30%, followed by male gender (53%), with average length of stay from 1 to 7 days (79%). The most frequent comorbidity was anaemia (30%). The antibiotic utilized was predominantly injectables (85%) given as monotherapy 85% and under the class of cephalosporin category (66%). Ceftriaxone (59%).Conclusion: was the most commonly used antibiotic. The findings of this study reveal that the antibiotic prescription for pediatric and adolescent pneumonia patients at Bhayangkara Lemdiklat Polri Hospital are in line with previous research results, where ceftriaxone is the most commonly used as a single-agent injectable antibiotic.